Antistatic nylon 5X resin and preparation method thereof

By using a combination of micro reactor and reactor in nylon polycondensation reaction, the reaction conditions are accurately controlled, and the problems of difficulty in controlling the temperature of nylon polymerization and poor antistatic properties are solved, and the molecular weight is achieved Improved uniformity and antistatic properties.

CN119219912AActive Publication Date: 2024-12-31PETROCHINA CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310792816.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

In the prior art, nylon polymerization needs to be carried out at high temperatures, and the reaction temperature is difficult to accurately control, resulting in uneven molecular weight distribution, high energy consumption, poor coupling stability between antistatic agents and nylon, and improved antistatic performance.

Method used

The nylon polycondensation reaction is carried out by a micro reactor, combined with a reactor, accurately control the reaction temperature and time, and the antistatic agents A and B are added for quantitative addition in batches, and the final polymerization and solid phase viscosity are increased to improve the degree of cross-linking and stability.

Benefits of technology

The production of nylon resin with uniform molecular weight is achieved, which reduces energy consumption, improves antistatic properties and stability, and avoids the risk of blockage of reaction equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004314077320000091
    Figure BDA0004314077320000091
  • Figure BDA0004314077320000101
    Figure BDA0004314077320000101
  • Figure BDA0004314077320000102
    Figure BDA0004314077320000102
Patent Text Reader

Abstract

The invention discloses antistatic nylon 5X resin and a preparation method thereof. The preparation method comprises the following steps: carrying out salt forming reaction on bio-based pentamethylene diamine and binary acid to obtain nylon 5X salt; carrying out prepolymerization reaction on the nylon 5X salt under the action of a catalyst to obtain a prepolymer; the prepolymer is introduced into a microreactor, an antistatic agent A is added, a final polymerization reaction is carried out, and nylon 5X resin is obtained; pressurizing the nylon 5X resin, introducing the nylon 5X resin into an extruder, adding an antistatic agent B and a tackifier for solid-phase tackifying, then carrying out traction bracing, introducing the nylon 5X resin into a granulator for granulating, and drying to obtain the antistatic nylon 5X resin slice. The problems that the polymerization temperature cannot be accurately controlled, the coupling stability of an antistatic agent and nylon is poor and the like are solved, and the antistatic performance of the obtained antistatic nylon 5X resin is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nylon preparation, and in particular to an antistatic nylon 5X resin and a preparation method thereof. Background Art

[0002] The raw materials of nylon 6 and nylon 66 products currently used in large quantities in industry are mainly produced by reprocessing byproducts of petroleum refining. They are highly dependent on petroleum and there are environmental pollution problems during the preparation and processing. The synthesis of new green and sustainable nylon has also become a hot topic in recent years. Using cheap and renewable biomass resources as raw materials and using bioengineering methods to synthesize the raw materials required for nylon to prepare bio-based nylon products has become one of the future development trends of nylon.

[0003] Bio-based nylon materials refer to the raw materials required for the production of nylon (generally dibasic acids, diamines or cyclic lactams) using renewable biomass resources such as glucose, cellulose, and vegetable oils (including castor oil, oleic acid and linoleic acid, etc.) obtained through bioengineering methods. Common bio-based nylon materials include nylon 56, nylon 510, nylon 5T, nylon 11, nylon 1010, nylon 610, nylon 410, nylon 1012, etc. Bio-based nylon has many applications in clothing fibers, natural gas pipelines, medical protective glasses, metal protective coatings, high-end fireproof oil and gas separators and crankshaft end covers, food packaging, automotive oil pipelines, LED packaging components, sports equipment and other fields.

[0004] Bio-based nylon 5X is comparable to nylon 6 and nylon 66, which are derived from petroleum. It has excellent heat resistance, wear resistance, impact resistance, tensile resistance and other properties. It can be widely used in various fields, and its output is increasing year by year. Traditional raw materials such as nylon 6 and nylon 66 are obtained by cracking petroleum. The raw material of synthetic bio-based nylon such as nylon 56 is 1,5-pentanediamine, which can be converted from lysine through bioengineering, which can significantly reduce dependence on petroleum. Nylon 56 has the advantages of high tensile strength and heat resistance, and can replace nylon 6 in the textile industry, automobile industry, and electrical and electronic industry. Nylon 56 fiber has high moisture absorption and release, good contact coldness, good wear resistance, strong spinnability, and high strength. However, if nylon 5X is used in the textile industry, it still needs to solve the problem of high static electricity content of the fabric. After contact or friction on its surface, it is very easy to accumulate a large amount of static electricity, and the generated charge cannot be released in time, which is very easy to cause static electricity hazards, and even disasters such as explosions. Therefore, the application of nylon 5X is limited by static electricity. Nylon 56 needs to be modified for antistatic properties to give it a lower resistance value, reduce the surface resistance and volume resistivity to a lower value, and eliminate the hazards of static electricity. Antistatic nylon 5X products can replace traditional nylon 6 and nylon 66 and will shine in the textile industry. If 40% of nylon 66 is replaced by bio-based nylon 56 in the future, its market size will reach 1.4 million tons / year, and the market prospects are broad. It is of great significance to carry out research and development of bio-based antistatic nylon 5X product preparation technology.

[0005] CN202211443232 discloses a halogen-free flame-retardant permanent antistatic polyamide composition, wherein a compatibilizer, a composite permanent antistatic masterbatch, a halogen-free flame retardant, a synergistic flame retardant, an antioxidant, and a lubricant are added to a polyamide resin in a weight ratio, and the mixture is blended and extruded to obtain a corresponding antistatic nylon composition.

[0006] CN202210979614 discloses an antistatic halogen-free flame-retardant reinforced nylon composite material. The preparation method is: after uniformly mixing the conductive microencapsulated hypophosphite flame retardant, antioxidant, glass fiber and nylon resin according to the required weight proportions, adding the mixture into a twin-screw extruder for melt blending and extrusion granulation, the antistatic halogen-free flame-retardant reinforced nylon composite material is obtained.

[0007] CN202211358594 discloses a low-temperature, wear-resistant, and antistatic polyamide composite material for the bottom material of a snowboard. First, the wear-resistant filler and the elastomer are kneaded, extruded, and pelletized to prepare a wear-resistant modified elastomer; then, the inorganic nanofiller, the conductive filler, and the antioxidant are added into a high-speed mixer for mixing; then, the polyamide matrix resin, the wear-resistant modified elastomer, the compatibilizer, and the wear-resistant polymer are added and continued to be mixed evenly to obtain a mixed material; finally, the mixed material and the inorganic fiber are added into a twin-screw extruder, melt-blended, extruded, cooled, air-dried, pelletized, and dried to prepare a low-temperature, wear-resistant, and antistatic polyamide composite material.

[0008] Although the above prior art provides a method for preparing antistatic nylon, the following problems still exist: (1) The initial nylon polymerization needs to be carried out at high temperature, and the reaction temperature of the reactor polymerization cannot be accurately controlled, which will lead to uneven molecular weight distribution of the nylon product and generate more energy consumption; (2) The currently prepared antistatic nylon is prepared by first preparing an antistatic agent and then blending and extruding it with the nylon material. The degree of cross-linking between the antistatic agent and the nylon material is still low, and the stability performance needs to be further improved; (3) The preparation method of the antistatic agent is still relatively complicated, and the antistatic performance still needs to be improved. Summary of the invention

[0009] The purpose of the present invention is to provide an antistatic nylon 5X resin and a preparation method thereof, so as to solve the problems existing in the prior art that the polymerization temperature cannot be accurately controlled and the coupling stability between the antistatic agent and nylon is poor, and the antistatic nylon 5X resin obtained by the present invention further improves the antistatic performance.

[0010] In order to achieve the above purpose, the present invention adopts the following technical solutions:

[0011] The present invention provides a method for preparing an antistatic nylon 5X resin, which comprises the following steps:

[0012] Bio-based pentamethylenediamine reacts with dibasic acid to form a salt to obtain nylon 5X salt;

[0013] The nylon 5X salt is subjected to a prepolymerization reaction under the action of a catalyst to obtain a prepolymer;

[0014] The prepolymer is introduced into a microreactor, and an antistatic agent A is added to carry out a final polymerization reaction to obtain a nylon 5X resin;

[0015] The nylon 5X resin is pressurized and introduced into an extruder, and an antistatic agent B and a tackifier are added for solid phase tackification, and then the strips are pulled and introduced into a pelletizer for pelletizing, and then dried to obtain antistatic nylon 5X resin chips.

[0016] In some embodiments of the present invention, the antistatic agent A, calculated based on 100 parts by total weight, includes: 45-60 parts of graphene, 5-10 parts of carbon black, 5-20 parts of nano calcium carbonate, 0.5-2 parts of antioxidant, 1-5 parts of dispersant and 5-20 parts of compatibilizer.

[0017] In some embodiments of the present invention, the amount of the antistatic agent A added is 20% to 30% of the mass of the nylon 5X salt solution.

[0018] In some embodiments of the present invention, the antioxidant may be selected from phosphite antioxidants, such as tris[2,4-di-tert-butylphenyl]phosphite.

[0019] In some embodiments of the present invention, the dispersant may be polyethylene low molecular weight wax or the like.

[0020] In some embodiments of the present invention, the compatibilizer may be maleic anhydride grafted POE or the like.

[0021] In some embodiments of the present invention, the antistatic agent B, calculated based on 100 parts by total weight, includes: 80-90 parts by weight of carbon nanotubes, 1-5 parts by weight of a dispersant, and 5-20 parts by weight of a compatibilizer.

[0022] In some embodiments of the present invention, the amount of the antistatic agent B added is 15-25% of the mass of the nylon 5X resin.

[0023] In some embodiments of the present invention, the dispersant may be polyethylene low molecular weight wax or the like.

[0024] In some embodiments of the present invention, the compatibilizer may be maleic anhydride grafted POE or the like.

[0025] In some embodiments of the present invention, the molar ratio of the bio-based pentamethylenediamine to the dibasic acid is 1:(1-1.2).

[0026] In some embodiments of the present invention, the dibasic acid is an aromatic or aliphatic dicarboxylic acid of C4 and above.

[0027] In some embodiments of the present invention, the dibasic acid is selected from one of adipic acid, undecanedioic acid, azelaic acid and terephthalic acid.

[0028] In some embodiments of the present invention, the salt-forming reaction is carried out in an alcohol solvent.

[0029] In some embodiments of the present invention, the alcohol solvent is selected from one or a combination of two or more of methanol, ethanol, n-propanol, isopropanol, n-butanol, 2-butanol, pentanol and octanol.

[0030] In some embodiments of the present invention, the temperature of the salt-forming reaction is 6 to 80° C. and the time is 0.5 to 2 h.

[0031] In some embodiments of the present invention, the process of the salt-forming reaction comprises:

[0032] In a protective gas atmosphere, bio-based pentamethylenediamine and dibasic acid are added to an alcohol solvent at a molar ratio of 1:(1-1.2), and a salt-forming reaction is carried out at 6-80° C. to obtain a nylon 5X salt mixed solution with a pH value of 6.5-7.5;

[0033] The obtained nylon 5X salt mixed solution is dried after removing the solvent to obtain the nylon 5X salt.

[0034] In some embodiments of the present invention, the solvent removal process includes: after preliminary filtering the obtained nylon 5X salt mixed solution, using a centrifuge to further remove the solvent; the rotation speed of the centrifuge is 3000-8000r / min, and the centrifugation time is 1-60min.

[0035] In some embodiments of the present invention, the drying temperature of the nylon 5X salt is 100-120° C., and the drying time is 1-6 hours.

[0036] In some embodiments of the present invention, the prepolymerization reaction is carried out in a water solvent, and the reaction container is a reactor; the nylon 5X salt, water and a catalyst are added together into the reactor to carry out the prepolymerization reaction.

[0037] In some embodiments of the present invention, in the prepolymerization reaction, the mass ratio of the nylon 5X salt to water is 1:(0.3-0.8).

[0038] In some embodiments of the present invention, the catalyst is anhydrous acetic acid, and the added amount is 0.3% to 2% of the mass of the nylon 5X salt solution.

[0039] In some embodiments of the present invention, the reaction temperature of the prepolymerization reaction is 120-160° C. and the reaction time is 0.5-2 h.

[0040] In some embodiments of the present invention, the microreactor is a falling film microreactor. Preferably, the falling film microreactor contains a multi-channel hollow structure made of stainless steel, the number of channels is 20 to 50, and a pressure control device is provided inside, and the control range is 0 to 10 MPa.

[0041] In some embodiments of the present invention, the reaction temperature of the final polymerization reaction is 220-260° C., and the reaction time is 1.5-3 h.

[0042] In some embodiments of the present invention, the tackifier is BASF nylon polyester tackifier ADR4370.

[0043] In some embodiments of the present invention, the added amount of the tackifier is 0.2% to 2% of the mass of the nylon 5X resin.

[0044] In some embodiments of the present invention, during the solid phase viscosity increasing process, the temperature is 200-280° C., the time is 1-6 hours, and the extruder speed is 100-800 rpm.

[0045] Another aspect of the present invention provides an antistatic nylon 5X resin, which is obtained by any of the above preparation methods.

[0046] In some embodiments of the present invention, the surface resistance of the antistatic nylon 5X resin is 10 7 ~10 10 Ω.

[0047] In some embodiments of the present invention, the surface resistance of the antistatic nylon 5X resin is 10 7 ~10 9 Ω.

[0048] In some embodiments of the present invention, the tensile strength of the antistatic nylon 5X resin is 80 to 100 GPa.

[0049] In some embodiments of the present invention, the tensile strength of the antistatic nylon 5X resin is 83-86 GPa.

[0050] In some embodiments of the present invention, the number average molecular weight of the antistatic nylon 5X resin is 20,000 to 40,000.

[0051] In some embodiments of the present invention, the molecular weight of the antistatic nylon 5X resin is 36,000 to 39,000 on average.

[0052] The beneficial effects of the present invention include:

[0053] 1) In view of the characteristics of nylon dehydration polycondensation, the present invention introduces a microreactor into the nylon polycondensation reaction. Compared with a reactor, a microreactor can effectively remove the heat of reaction, accurately control the reaction temperature, achieve effective requirements for residence time, control the concentration distribution of reactants, and at the same time, the antistatic agent and the nylon prepolymer can be better cross-linked, and finally produce a nylon resin with uniform molecular weight, and further save energy consumption, improve the efficiency of the reaction, and save reaction time. The present invention also adopts a reactor plus a microreactor, which can effectively control the reaction rhythm, make the reaction more complete, and the reaction is also safer.

[0054] 2) In order to solve the problem that nylon has too high viscosity and is easy to stick to the wall and clog the reactor, the present invention carries out the solid phase viscosity increase process of nylon after it is introduced into the extruder. Compared with the reactor, the reaction conditions of the extruder are milder and more controllable, which can make the molecular weight of nylon grow steadily, and then it can be directly pulled and extruded without causing clogging problems.

[0055] 3) In order to solve the problem of unstable antistatic effect of nylon, the present invention designs two antistatic agents and adds them into the nylon final polymerization and solid phase viscosity enhancement steps separately, batchwise and quantitatively, so that the antistatic agents can be better coupled with nylon, the antistatic effect is better, and the antistatic performance is more stable. DETAILED DESCRIPTION

[0056] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0057] The invention provides a novel polymerization method for antistatic nylon 5X. By adding a microreactor to a reactor, the time, temperature and concentration distribution of reactants of a nylon polycondensation reaction are controlled, so that the molecular weight of nylon can be evenly distributed, the polymerization efficiency is higher, the antistatic performance is more stable, the reaction efficiency is improved, and the reaction energy consumption is reduced. The risk of blockage of the reaction equipment is reduced by solid phase viscosity enhancement in an extruder. The antistatic ability and stability of nylon 5X are improved by adding different types of antistatic agents in batches during the nylon polymerization reaction. A more feasible method is provided for efficiently producing antistatic nylon 5X resin with better performance.

[0058] The preparation method of the antistatic nylon 5X resin provided by the present invention comprises the following steps:

[0059] S1, bio-based pentamethylenediamine reacts with a dibasic acid to form a salt to obtain nylon 5X salt;

[0060] S2, the nylon 5X salt is subjected to a prepolymerization reaction under the action of a catalyst to obtain a prepolymer;

[0061] S3, the prepolymer is introduced into a microreactor, and an antistatic agent A is added to carry out a final polymerization reaction to obtain a nylon 5X resin;

[0062] S4, the nylon 5X resin is pressurized and introduced into an extruder, and an antistatic agent B and a tackifier are added for solid phase tackification, and then the strips are pulled and introduced into a pelletizer for pelletizing, and antistatic nylon 5X resin chips are obtained after drying.

[0063] The following is a detailed description of each step:

[0064] S1. Bio-based pentamethylenediamine reacts with a dibasic acid to form a salt to obtain nylon 5X salt.

[0065] Wherein, the molar ratio of the bio-based pentamethylenediamine to the dibasic acid is preferably 1:(1-1.2).

[0066] Preferably, the dicarboxylic acid is an aromatic or aliphatic dicarboxylic acid of C4 or above; for example, it can be selected from one of adipic acid, undecane dicarboxylic acid, azelaic acid, and terephthalic acid.

[0067] In some specific embodiments of the present invention, the salt-forming reaction is carried out in an alcohol solvent. Preferably, the alcohol solvent is selected from one or a combination of two or more of methanol, ethanol, n-propanol, isopropanol, n-butanol, 2-butanol, pentanol, and octanol.

[0068] In some specific embodiments of the present invention, the temperature of the salt-forming reaction is 6 to 80° C., and the time is 0.5 to 2 h.

[0069] In some specific embodiments of the present invention, the process of the salt-forming reaction comprises:

[0070] In a protective gas atmosphere, bio-based pentamethylenediamine and dibasic acid are added to an alcohol solvent at a molar ratio of 1:(1-1.2), and a salt-forming reaction is carried out at 6-80° C. to obtain a nylon 5X salt mixed solution with a pH value of 6.5-7.5;

[0071] The obtained nylon 5X salt mixed solution is dried after removing the solvent to obtain the nylon 5X salt.

[0072] Specifically, the solvent removal can be achieved by filtering, centrifuging, etc. The drying can be carried out in an oven, etc., and the drying temperature is specifically determined by the solvent used. The protective gas atmosphere can be formed by using protective gas to perform multiple gas replacements on the reaction container, or by continuously introducing protective gas during the reaction process, or by any other method that can form a protective gas atmosphere. The protective gas is a rare gas such as nitrogen or argon.

[0073] In some specific embodiments of the present invention, the solvent removal process includes: after preliminary filtering the obtained nylon 5X salt mixed solution, using a centrifuge to further remove the solvent; the rotation speed of the centrifuge is 3000-8000r / min, and the centrifugation time is 1-60min.

[0074] In some specific embodiments of the present invention, the drying temperature of the nylon 5X salt is 100-120° C., and the drying time is 1-6 hours.

[0075] S2. The nylon 5X salt is subjected to a prepolymerization reaction under the action of a catalyst to obtain a prepolymer.

[0076] Preferably, the prepolymerization reaction is carried out in a water solvent, and the reaction container is a reactor; the nylon 5X salt, water and a catalyst are added together into the reactor for prepolymerization reaction. The mass ratio of the nylon 5X salt to water is preferably 1:(0.3-0.8).

[0077] In some specific embodiments of the present invention, the catalyst is anhydrous acetic acid, and the added amount is 0.3% to 2% of the mass of the nylon 5X salt solution.

[0078] In some specific embodiments of the present invention, the reaction temperature of the prepolymerization reaction is 120-160° C. and the reaction time is 0.5-2 h.

[0079] In some specific embodiments of the present invention, the antistatic agent A is calculated based on 100 parts by total weight and includes: 45-60 parts of graphene, 5-10 parts of carbon black, 5-20 parts of nano calcium carbonate, 0.5-2 parts of antioxidant, 1-5 parts of dispersant and 5-20 parts of compatibilizer. In some specific embodiments of the present invention, the antioxidant is selected from phosphite antioxidants, such as tris[2,4-di-tert-butylphenyl]phosphite; the dispersant is polyethylene low molecular wax, etc., and the compatibilizer is maleic anhydride grafted POE, etc.

[0080] The nano calcium carbonate itself has a conductive effect and also has a certain compatibility effect, which promotes its compatibility with graphene and carbon black, increases compatibility, and can increase the antistatic effect.

[0081] In some specific embodiments of the present invention, the amount of the antistatic agent A added is 20% to 30% of the mass of the nylon 5X salt solution.

[0082] S3, the prepolymer is introduced into a microreactor, and an antistatic agent A is added to carry out a final polymerization reaction to obtain nylon 5X resin.

[0083] The microreactor is preferably a falling film microreactor. More preferably, the falling film microreactor contains a multi-channel hollow structure made of stainless steel, the number of channels is 20 to 50, and a pressure control device is provided therein, and the control range is 0 to 10 MPa.

[0084] In some specific embodiments of the present invention, the reaction temperature of the final polymerization reaction is 220-260° C., and the reaction time is 1.5-3 h.

[0085] S4, the nylon 5X resin is pressurized and introduced into an extruder, and an antistatic agent B and a tackifier are added for solid phase tackification, and then the strips are pulled and introduced into a pelletizer for pelletizing, and antistatic nylon 5X resin chips are obtained after drying.

[0086] In some specific embodiments of the present invention, the added amount of the tackifier is 0.2% to 2% of the mass of the nylon 5X resin.

[0087] In some specific embodiments of the present invention, during the solid phase viscosity increasing process, the temperature is 200-280° C., the time is 1-6 hours, and the speed of the extruder is 100-800 rpm.

[0088] The tackifier may be any conventional tackifier in the art, for example, BASF nylon polyester tackifier ADR4370 is selected in some specific embodiments of the present invention.

[0089] In some specific embodiments of the present invention, the antistatic agent B is calculated based on 100 parts by total weight and includes: 80-90 parts of carbon nanotubes, 1-5 parts of dispersant and 5-20 parts of compatibilizer. In some specific embodiments of the present invention, the dispersant is polyethylene low molecular wax, etc., and the compatibilizer is maleic anhydride grafted POE, etc.

[0090] In the present invention, the antistatic agent A and the antistatic agent B are added in the prepolymerization reaction and the solid phase viscosity enhancement reaction, respectively. The carbon nanotubes in the antistatic agent B have poor compatibility with the carbon black and graphene in the antistatic agent A. In addition, if the antistatic agent A and the antistatic agent B are added together in the early stage, the reaction environment is not favorable for the carbon nanotubes, and it is not easy for them to exert their antistatic properties.

[0091] In some specific embodiments of the present invention, the added amount of the antistatic agent B is 15-25% of the mass of the nylon 5X resin.

[0092] The antistatic nylon 5X resin obtained by any of the above preparation methods preferably has a surface resistance value of 10 7 ~10 10 Ω, more preferably 10 7 ~10 9 Ω; the tensile strength of the antistatic nylon 5X resin is preferably 80 to 100 GPa, more preferably 83 to 86 GPa; the number average molecular weight of the antistatic nylon 5X resin is preferably 20,000 to 40,000, more preferably 36,000 to 39,000.

[0093] Some specific examples are provided below for illustration, wherein all numerical values ​​specified (such as temperature, time, concentration and weight, etc., including the range of each thereof) are generally approximate values ​​that can be appropriately changed (+) or (-) in increments of 0.1 or 1.0. All numerical values ​​specified can be understood as being preceded by the term "about".

[0094] The formula of the antistatic agent A used in the following Examples 1-12 and Comparative Examples is: 60 parts of graphene, 10 parts of carbon black, 10 parts of nano calcium carbonate, 2 parts of antioxidant, 3 parts of dispersant and 15 parts of compatibilizer. The antioxidant is tris[2,4-di-tert-butylphenyl]phosphite, the dispersant is polyethylene low molecular weight wax, and the compatibilizer is maleic anhydride grafted POE.

[0095] The formula of antistatic agent B is: 90 parts of carbon nanotubes, 5 parts of dispersant and 5 parts of compatibilizer. The dispersant is polyethylene low molecular wax, and the compatibilizer is maleic anhydride grafted POE.

[0096] The tackifier is specifically BASF nylon polyester tackifier ADR4370.

[0097] Example 1

[0098] The following examples are all carried out on the basis of this experimental procedure, including:

[0099] S1. Take 73.07g (0.5mol) of adipic acid and put it into 400mL of anhydrous ethanol. Heat it to 65°C and stir it. After the adipic acid is dissolved, slowly drop 51.09g (0.5mol) of bio-based pentamethylenediamine under nitrogen protection. Continue to stir and react at 65°C for 1h. Stop the reaction when the solution becomes turbid. At this time, the pH value of the solution is measured to be 6.9.

[0100] The solution was slowly poured into a funnel with filter paper for preliminary filtration, and the filtered mixed solution was poured into a centrifuge for further centrifugal separation and filtration. The centrifuge speed was 6000 r / min and the centrifugation time was 40 min. The obtained white powder was collected and placed in an oven at a drying temperature of 100 ° C and a drying time of 3 h to obtain white granular nylon 56 salt.

[0101] S2. Take 100g of nylon 56 salt and 50g of pure water and put them into a reactor. Add 1.5g of anhydrous acetic acid. Pass nitrogen three times until there is no air in the reactor. Under nitrogen protection, perform prepolymerization at 140°C. After 1h of reaction, obtain prepolymer nylon 56 melt.

[0102] S3. The nylon 56 melt is introduced into a falling film microreactor, and 45 g of antistatic agent A is added. After reacting at 240° C. for 3 h, a nylon 56 melt resin is obtained.

[0103] S4, continue to pass the nylon 56 molten resin into the extruder, and add 2.8g of tackifier and 45g of antistatic agent B, and perform solid phase viscosity enhancement in the extruder, wherein during the solid phase viscosity enhancement, the extruder speed is 500rpm, and the reaction is carried out in the extruder for 5h, and then the resin is passed into a pelletizer for pelletizing, and antistatic nylon 5X resin chips are obtained after drying.

[0104] Table 1 shows the quality of the nylon product, its number average molecular weight and tensile strength obtained by changing the molar ratio of adipic acid and pentamethylenediamine according to the above experimental conditions.

[0105] Table 1

[0106]

[0107]

[0108] From the data in Table 1, it can be seen that when the molar ratio of diamine to diacid is 1:(1.1-1.2), the molecular weight of the obtained nylon resin ranges from 35000 to 39000, and the tensile strength ranges from 83 to 86 GPa.

[0109] Example 2

[0110] Example 2 is similar to Example 1-2, except that the mass ratio of nylon 56 salt to pure water placed in the reactor is different. In Example 2, the mass ratio of nylon 56 salt to pure water is changed, and the data of the mass of the nylon product obtained, its number average molecular weight and tensile strength are shown in Table 2.

[0111] Table 2

[0112]

[0113] From the data in Table 2, it can be seen that when the mass ratio of nylon 56 salt to pure water is 1:(0.5-0.8), the molecular weight of the obtained nylon resin ranges from 37000 to 39000, and the tensile strength ranges from 83 to 86 GPa.

[0114] Example 3

[0115] Example 3 is similar to Example 2-2, except that the mass of the catalyst anhydrous acetic acid added in the reactor is different. In Example 3, the amount of anhydrous acetic acid added is changed, and the data of the mass of the nylon product obtained, its number average molecular weight and tensile strength are shown in Table 3.

[0116] Table 3

[0117]

[0118] From the data in Table 3, it can be seen that when the ratio of the amount of anhydrous acetic acid added to the mass of nylon 56 salt solution is 1%, the molecular weight of the nylon resin ranges from 38000 to 39000, and the tensile strength ranges from 84 to 86 GPa.

[0119] Example 4

[0120] Example 4 is similar to Example 3-2, the only difference being that the reaction temperature for the prepolymerization reaction in the reactor is different. In Example 4, the reaction temperature of the prepolymerization reaction in the reactor is changed, the pressure in the reactor, and the quality of the nylon product finally obtained, its number average molecular weight, and tensile strength are shown in Table 4.

[0121] Table 4

[0122]

[0123] From the data in Table 4, it can be seen that when the prepolymerization temperature in the reactor is 120-140°C, the molecular weight of the nylon resin is in the range of 38,000-39,000, and the tensile strength is in the range of 84-86 GPa.

[0124] Example 5

[0125] Example 5 is similar to Example 4-2, the only difference being that the reaction time for the prepolymerization reaction in the reactor is different. In Example 4, the reaction time for the prepolymerization reaction in the reactor is changed, and the data on the quality of the nylon product finally obtained, its number average molecular weight, and tensile strength are shown in Table 5.

[0126] Table 5

[0127]

[0128] It can be seen from the data in Table 5 that when the prepolymerization time in the reactor is 0.5 to 2 hours, the molecular weight of the nylon resin is in the range of 37000 to 39000, and the tensile strength is in the range of 83 to 86 GPa.

[0129] Example 6

[0130] Example 6 is similar to Example 5-3, except that the mass of the antistatic agent A added in the falling film microreactor is different. In Example 6, the mass of the antistatic agent A added in the falling film microreactor is changed, and the data of the quality of the nylon product, its number average molecular weight, tensile strength and surface resistance of the resin material finally obtained are shown in Table 6.

[0131] Table 6

[0132]

[0133] From the data in Table 6, it can be seen that when the amount of antistatic agent A added accounts for 20% to 30% of the nylon salt solution, the molecular weight of the nylon resin is in the range of 37000 to 39000, the tensile strength is in the range of 85 to 86 GPa, and the resistance value of the nylon resin is 10 8 ~10 10 Ω.

[0134] Example 7

[0135] Example 7 is similar to Example 6-3, the only difference being that the reaction temperature for the final polymerization reaction in the falling film microreactor is different. In Example 7, the reaction temperature of the final polymerization reaction in the falling film microreactor, the pressure in the reaction tube, and the quality of the nylon product finally obtained, its number average molecular weight, and tensile strength are shown in Table 7.

[0136] Table 7

[0137]

[0138] It can be seen from the data in Table 7 that when the reaction temperature of the final polymerization reaction in the microreactor is 220-260°C, the molecular weight of the nylon resin is in the range of 38000-39000, and the tensile strength is in the range of 84-86 GPa.

[0139] Example 8

[0140] Example 8 is similar to Example 7-2, the only difference being that the reaction time for the final polymerization reaction in the falling film microreactor is different. In Example 8, the reaction time for the final polymerization reaction in the reaction tube is changed, and the data on the quality of the nylon product obtained, its number average molecular weight, and tensile strength are shown in Table 8.

[0141] Table 8

[0142]

[0143] It can be seen from the data in Table 8 that when the reaction time of the final polymerization reaction in the microreactor is 1.5 to 3 hours, the molecular weight of the nylon resin is in the range of 37000 to 39000, and the tensile strength is in the range of 84 to 86 GPa.

[0144] Example 9

[0145] Example 9 is similar to Example 8-3, the only difference being that the mass of the thickener added during solid phase thickening in the extruder is different. In Example 9, the mass of the thickener added is changed, and the data of the mass of the nylon product finally obtained, its number average molecular weight, and tensile strength are shown in Table 9.

[0146] Table 9

[0147]

[0148] It can be seen from the data in Table 9 that when the ratio of the tackifier added to the nylon 56 resin is 2%, the molecular weight of the nylon resin is in the range of 36000 to 39000, and the tensile strength is in the range of 84 to 87 GPa.

[0149] Example 10

[0150] Example 10 is similar to Example 9-3, the only difference being that the reaction temperature is different when solid phase viscosity enhancement is performed in the extruder. In Example 10, the reaction temperature of the extruder is changed, and the data of the quality of the nylon product finally obtained, its number average molecular weight, and tensile strength are shown in Table 10.

[0151] Table 10

[0152]

[0153] From the data in Table 10, it can be seen that when the solid phase viscosity increasing reaction temperature is 240°C, the molecular weight of the nylon resin is in the range of 38,000 to 39,000, and the tensile strength is in the range of 84 to 86 GPa.

[0154] Embodiment 11

[0155] Example 11 is similar to Example 10-2, the only difference being the reaction time of solid phase viscosity enhancement in the extruder. In Example 11, the reaction time of solid phase viscosity enhancement in the extruder was changed, and the data of the quality of the nylon product finally obtained, its number average molecular weight, and tensile strength are shown in Table 11.

[0156] Table 11

[0157]

[0158] It can be seen from the data in Table 11 that when the solid phase viscosity increasing reaction time is 1 to 5 hours, the molecular weight of the nylon resin is in the range of 36000 to 39000, and the tensile strength is in the range of 83 to 86 GPa.

[0159] Example 12

[0160] Example 12 is similar to Example 11-3, the only difference being that the mass of the antistatic agent B added in the extruder is different. In Example 12, the mass of the antistatic agent B added in the extruder is changed, and the data of the mass of the nylon product, its number average molecular weight, tensile strength and surface resistance of the resin material finally obtained are shown in Table 12.

[0161] Table 12

[0162]

[0163] From the data in Table 12, it can be seen that when the amount of antistatic agent B added is 15% to 25% of the nylon salt solution, the molecular weight of the nylon resin is in the range of 37000 to 39000, the tensile strength is in the range of 85 to 86 GPa, and the resistance value is 10 7 ~10 10 Ω.

[0164] Example 13

[0165] Example 13 is similar to Example 6-3, except that the composition ratio of the antistatic agent A added in the falling film microreactor is different. In Example 13, the composition ratio of the antistatic agent A added in the falling film microreactor is changed, that is, the ratio of graphene, carbon black and nano-calcium carbonate in the antistatic agent A is changed. The data of the quality of the nylon product, its number average molecular weight, tensile strength and surface resistance of the resin material finally obtained are shown in Tables 13 and 14.

[0166] Table 13

[0167]

[0168] In Table 13, the ratio of graphene to carbon black in antistatic agent A remains unchanged at 6:1. From the data in Table 13, it can be seen that when the addition amount of antistatic agent A is 55% to 70%, the molecular weight of nylon resin is in the range of 38000 to 39000, the tensile strength is in the range of 85 to 86 GPa, and the resistance value is 10 8 ~10 10 Ω.

[0169] Table 14

[0170]

[0171] From the data in Table 14, it can be seen that when the proportion of calcium carbonate in antistatic agent A is 5% to 20%, the molecular weight of nylon resin is in the range of 38000 to 39000, the tensile strength is in the range of 85 to 86 GPa, and the resistance value is 10 8 ~10 10 Ω.

[0172] Embodiment 14

[0173] Example 14 is similar to Example 12-3, except that the composition ratio of the antistatic agent B added in the extruder is different. In Example 14, the composition ratio of the antistatic agent B added in the extruder is changed, that is, the ratio of carbon nanotubes in the antistatic agent B is changed. The data of the quality of the nylon product, its number average molecular weight, tensile strength and surface resistance of the resin material finally obtained are shown in Table 15.

[0174] Table 15

[0175]

[0176] From the data in Table 14, it can be seen that when the addition ratio of carbon nanotubes in antistatic agent B is 80% to 90%, the molecular weight of nylon resin is in the range of 38000 to 39000, the tensile strength is in the range of 85 to 86 GPa, and the resistance value is 10 7 ~10 8 Ω.

[0177] Comparative Example 1

[0178] In this comparative example, the final polymerization reaction was carried out in a reactor.

[0179] S1. Take 73.07g of adipic acid and put it into 400mL of anhydrous ethanol. Heat it to 65°C and stir it. After the adipic acid is dissolved, slowly drop 51.09g of bio-based pentamethylenediamine under nitrogen protection. Continue to stir and react at 65°C for 1h. Stop the reaction when the solution becomes turbid. At this time, the pH value of the solution is measured to be 6.9.

[0180] The solution was slowly poured into a funnel with filter paper for preliminary filtration, and the filtered mixed solution was poured into a centrifuge for further centrifugal separation and filtration. The centrifuge speed was 6000 r / min and the centrifugation time was 40 min. The obtained white powder was collected and placed in an oven at a drying temperature of 100 ° C and a drying time of 3 h to obtain white granular nylon 56 salt.

[0181] S2. Take 100g of nylon 56 salt, 50g of pure water and 45g of antistatic agent A and put them into a reactor, and add 1.5g of anhydrous acetic acid. Pass nitrogen three times until there is no air in the reactor. Under nitrogen protection, prepolymerize at 140℃. After reacting for 1h, heat to 240℃ and continue polymerization for 3h to obtain nylon 56 molten resin.

[0182] S3, continue to pass the nylon 56 molten resin into the extruder, and add 2.8g of tackifier and 45g of antistatic agent B to perform solid phase viscosity enhancement in the extruder, wherein during the solid phase viscosity enhancement, the extruder speed is 500rpm, react in the extruder for 5h, then pressurize and pass into a pelletizer for pelletizing, and obtain antistatic nylon 5X resin chips after drying.

[0183] In this comparative example, all the above conditions were the same, and only the final polymerization step was changed. The mass of the obtained nylon 56 resin was 134.12 g, the number average molecular weight of nylon was 37,000, and the tensile strength was 80.43 GPa.

[0184] It can be seen from the comparison between this comparative example and Example 1 that, under the condition that the final polymerization reaction is carried out in a reactor under the same other conditions, the yield of the final nylon product, as well as the number average molecular weight and tensile strength are reduced.

[0185] Comparative Example 2

[0186] In this comparative example, only solid phase viscosity enhancement was performed in a falling film microreactor and an antistatic agent B was added.

[0187] S1. Take 73.07g of adipic acid and put it into 400mL of anhydrous ethanol. Heat it to 65°C and stir it. After the adipic acid is dissolved, slowly drop 51.09g of bio-based pentamethylenediamine under nitrogen protection. Continue to stir and react at 65°C for 1h. Stop the reaction when the solution becomes turbid. At this time, the pH value of the solution is measured to be 6.9.

[0188] The solution was slowly poured into a funnel with filter paper for preliminary filtration, and the filtered mixed solution was poured into a centrifuge for further centrifugal separation and filtration. The centrifuge speed was 6000 r / min and the centrifugation time was 40 min. The obtained white powder was collected and placed in an oven at a drying temperature of 100 ° C and a drying time of 3 h to obtain white granular nylon 56 salt.

[0189] S2, 100g of nylon 56 salt and 50g of pure water were placed in a reaction kettle, and 1.5g of anhydrous acetic acid was added dropwise. Nitrogen was passed through the kettle three times until there was no air in the kettle. Under nitrogen protection, a prepolymerization reaction was carried out. After the reaction was carried out for 1 hour, a prepolymer nylon 56 melt was obtained.

[0190] S3. The nylon 56 melt is introduced into a falling film microreactor, and 45 g of antistatic agent A, 45 g of antistatic agent B and 2.8 g of tackifier are added. After reacting in the falling film microreactor for 3 hours, an antistatic nylon 56 melt resin is obtained.

[0191] S4, the antistatic nylon 56 molten resin is continuously pressurized and passed into the extruder, the extruder speed is 500 rpm, the extruder temperature is 240°C, after 5 hours in the extruder, it is then passed into a pelletizer for pelletizing, and the antistatic nylon 5X resin chips are obtained after drying.

[0192] In this comparative example, under the same conditions as above, only the addition steps of solid phase viscosity enhancement and antistatic agent B were changed, and they were added together with antistatic agent A in the final polymerization reaction. The compatibility of the two antistatic agents added together was poor. The mass of the obtained nylon 56 resin was 137.12 g, the number average molecular weight of nylon was 37000, the tensile strength was 81.77 GPa, and the surface resistance of the resin was 10 9 Ω.

[0193] In this comparative example, under the same conditions as above, except that the steps of adding the tackifier and the antistatic agent B are changed, the yield of the nylon product finally obtained, as well as the number average molecular weight and tensile strength are reduced, and the surface resistance of the resin is increased.

[0194] Comparative Example 3

[0195] In this comparative example, no antistatic agent A was added, and other processes remained unchanged.

[0196] S1. Take 73.07g of adipic acid and put it into 400mL of anhydrous ethanol. Heat it to 65°C and stir it. After the adipic acid is dissolved, slowly drop 51.09g of bio-based pentamethylenediamine under nitrogen protection. Continue to stir and react at 65°C for 1h. Stop the reaction when the solution becomes turbid. At this time, the pH value of the solution is measured to be 6.9.

[0197] The solution was slowly poured into a funnel with filter paper for preliminary filtration, and the filtered mixed solution was poured into a centrifuge for further centrifugal separation and filtration. The centrifuge speed was 6000 r / min and the centrifugation time was 40 min. The obtained white powder was collected and placed in an oven at a drying temperature of 100 ° C and a drying time of 3 h to obtain white granular nylon 56 salt.

[0198] S2. Take 100g of nylon 56 salt and 50g of pure water and put them into a reactor. Add 1.5g of anhydrous acetic acid dropwise. Pass nitrogen three times until there is no air in the reactor. Under nitrogen protection, conduct a preliminary pre-reaction at 140°C. After reacting for 1h, a preliminary nylon 56 melt is obtained.

[0199] S3, introducing the nylon 56 melt into a falling film microreactor, and reacting at 240° C. for 3 hours to obtain a nylon 56 molten resin.

[0200] S4, continue to pass the nylon 56 molten resin into the extruder, and add 2.8g of tackifier and 45g of antistatic agent B, and perform solid phase viscosity enhancement in the extruder, wherein during the solid phase viscosity enhancement, the extruder speed is 500rpm, and the reaction is carried out in the extruder for 5h, and then the resin is passed into a pelletizer for pelletizing, and antistatic nylon 5X resin chips are obtained after drying.

[0201] In this comparative example, under the same conditions as above, no antistatic agent A was added, and the surface resistance of the nylon 56 resin obtained was 10 10 Ω, proving that antistatic agent A can more effectively reduce the surface resistance of nylon 56 resin.

[0202] Comparative Example 4

[0203] In this comparative example, no antistatic agent B was added, and other processes remained unchanged.

[0204] S1. Take 73.07g of adipic acid and put it into 400mL of anhydrous ethanol. Heat it to 65°C and stir it. After the adipic acid is dissolved, slowly drop 51.09g of bio-based pentamethylenediamine under nitrogen protection. Continue to stir and react at 65°C for 1h. Stop the reaction when the solution becomes turbid. At this time, the pH value of the solution is measured to be 6.9.

[0205] The solution was slowly poured into a funnel with filter paper for preliminary filtration, and the filtered mixed solution was poured into a centrifuge for further centrifugal separation and filtration. The centrifuge speed was 6000 r / min and the centrifugation time was 40 min. The obtained white powder was collected and placed in an oven at a drying temperature of 100 ° C and a drying time of 3 h to obtain white granular nylon 56 salt.

[0206] S2. Take 100g of nylon 56 salt and 50g of pure water and put them into a reactor. Add 1.5g of anhydrous acetic acid dropwise. Pass nitrogen three times until there is no air in the reactor. Under nitrogen protection, conduct a preliminary pre-reaction at 140°C. After reacting for 1h, a preliminary nylon 56 melt is obtained.

[0207] S3. The nylon 56 melt is introduced into a falling film microreactor, and 45 g of antistatic agent A is added. After reacting at 240° C. for 3 h, a nylon 56 melt resin is obtained.

[0208] S4, continue to introduce the nylon 56 molten resin into the extruder, and add 2.8g of tackifier to perform solid phase tackification in the extruder, wherein during the solid phase tackification, the extruder speed is 500rpm, react in the extruder for 5h, then introduce it into the pelletizer for pelletizing, and obtain antistatic nylon 5X resin chips after drying.

[0209] In this comparative example, under the same conditions as above, no antistatic agent B was added, and the surface resistance of the nylon 56 resin obtained was 10 10 Ω, proving that antistatic agent B can more effectively reduce the surface resistance of nylon 56 resin.

[0210] The tensile strength involved in the above embodiments and comparative examples was measured by a universal tensile machine, the number average molecular weight was measured by GPC gel chromatography, and the surface resistance of the resin material was measured by a surface resistance tester.

[0211] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A method for preparing an antistatic nylon 5X resin, wherein: The preparation method comprises the following steps: Bio-based pentamethylenediamine reacts with dibasic acid to form a salt to obtain nylon 5X salt; The nylon 5X salt is subjected to a prepolymerization reaction under the action of a catalyst to obtain a prepolymer; The prepolymer is introduced into a microreactor, and an antistatic agent A is added to carry out a final polymerization reaction to obtain a nylon 5X resin; The nylon 5X resin is pressurized and introduced into an extruder, and an antistatic agent B and a tackifier are added for solid phase tackification, and then the strips are pulled and introduced into a pelletizer for pelletizing, and then dried to obtain antistatic nylon 5X resin chips.

2. The preparation method according to claim 1, wherein The antistatic agent A, calculated based on 100 parts by total weight, includes: 45-60 parts of graphene, 5-10 parts of carbon black, 5-20 parts of nano calcium carbonate, 0.5-2 parts of antioxidant, 1-5 parts of dispersant and 5-20 parts of compatibilizer.

3. The preparation method according to claim 1, wherein The added amount of the antistatic agent A is 20% to 30% of the mass of the nylon 5X salt solution.

4. The preparation method according to claim 1, wherein The antistatic agent B, calculated based on 100 parts by total weight, includes: 80-90 parts by weight of carbon nanotubes, 1-5 parts by weight of dispersant and 5-20 parts by weight of compatibilizer.

5. The preparation method according to claim 1, wherein The added amount of the antistatic agent B is 15-25% of the mass of the nylon 5X resin.

6. The preparation method according to claim 1, wherein The molar ratio of the bio-based pentamethylenediamine to the dibasic acid is 1:(1-1.2).

7. The preparation method according to claim 1, wherein The dicarboxylic acid is an aromatic or aliphatic dicarboxylic acid of C4 or above.

8. The preparation method according to claim 1, wherein The dibasic acid is selected from one of adipic acid, undecanedioic acid, azelaic acid and terephthalic acid.

9. The preparation method according to claim 1, wherein The salt-forming reaction is carried out in an alcohol solvent; the alcohol solvent is selected from one or a combination of two or more of methanol, ethanol, n-propanol, isopropanol, n-butanol, 2-butanol, pentanol and octanol.

10. The preparation method according to claim 1, wherein: The process of the salt-forming reaction comprises: In a protective gas atmosphere, bio-based pentamethylenediamine and dibasic acid are added to an alcohol solvent at a molar ratio of 1:(1-1.2), and a salt-forming reaction is carried out at 6-80° C. for 0.5-2 hours to obtain a nylon 5X salt mixed solution with a pH value of 6.5-7.5; The obtained nylon 5X salt mixed solution is dried after removing the solvent to obtain the nylon 5X salt.

11. The preparation method according to claim 1, wherein: The prepolymerization reaction is carried out in a water solvent, and the reaction container is a reactor; the nylon 5X salt, water and a catalyst are added together into the reactor to carry out the prepolymerization reaction; the mass ratio of the nylon 5X salt to water is 1:(0.3-0.8).

12. The preparation method according to claim 1, wherein: The catalyst is anhydrous acetic acid, and the added amount is 0.3% to 2% of the mass of the nylon 5X salt solution.

13. The preparation method according to claim 1, wherein The reaction temperature of the prepolymerization reaction is 120-160° C., and the reaction time is 0.5-2 h.

14. The preparation method according to claim 1, wherein: The microreactor is a falling film microreactor.

15. The preparation method according to claim 1, wherein: The reaction temperature of the final polymerization reaction is 220-260° C., and the reaction time is 1.5-3 hours.

16. The preparation method according to claim 1, wherein: The added amount of the tackifier is 0.2% to 2% of the mass of the nylon 5X resin.

17. The preparation method according to claim 1, wherein: During the solid phase viscosity enhancement process, the temperature is 200-280° C. and the time is 1-6 hours.

18. An antistatic nylon 5X resin obtained by the preparation method according to any one of claims 1 to 17.

19. The antistatic nylon 5X resin according to claim 18, wherein The surface resistance of the antistatic nylon 5X resin is 10 7 ~10 10 Ω, tensile strength is 80-100 GPa, and number average molecular weight is 20,000-40,000.

Citation Information

Patent Citations

  • High temperature-resistant nylon / polybutylece terephthalate (PBT) / polyethylene terephthalate (PET) copolymer, and preparation method and application thereof

    CN102660019A

  • Production method of antistatic nylon 56 fibers

    CN111321481A

  • Antistatic halogen-free flame-retardant reinforced nylon composite material and preparation method thereof

    CN115216142A

  • Method for preparing bio-based semi-aromatic polyamide based on micro-reaction device

    CN116284756A

  • Long-term antistatic composition

    US6072001A